Science Teachers Competence in Utilize Learning Resources at Junior High Schools - Faradiba, Deby Gemysa; Budiningsih, C Asri (Unnes Science Education Journal, 2020)
This study aimed to determine: (1) learning resources used by science teachers, (2) the ability of science teachers to utilize learning resources, and (3) the implications of using learning resources on the quality of science teachers in the learning process. This study was a field study with a qualitative approach. The subjects of this study was science teachers at SMP N 3 Purworejo. Techniques used in data analysis was an interactive model by Miles & Huberman including data collection, data reduction, data display, and conclusion. The result showed that learning resources used by science teachers include in the environment around the school, the environment around the residence of learners, and learning outside of school. The ability of science teachers to utilize learning resources, overall all science teachers of SMP Negeri 3 Purworejo was able to use it. Implications use of learning resources on the quality of science teachers in learning process was teacher able to give more motivation, maximize learning time, and maximize creativity.